FREEDOM OF INFORMATION ACT AND JOURNALISM IN NIGERIA 2011 - 2021: A REVIEW OF A DECADE OF UTILISATION AND PRACTICE - Asogwa , Fidelis Ndidiamaka; Ibe , Nkechinyere Magdalene Awo; Orji-Egwu , Agatha Obiageri (The Melting Pot, 2021)
Freedom of Information (FOI) is one of the globally recognised instruments in democratic societies specifically designed to enhance journalism practice and enthrone an open society. Nigeria joined the rest of the world in 2011 to enact a freedom of information act. But the extent of the workability of this act, and its utilisation among journalists has not been fully explored or understood. What is the level of FOI knowledge among journalists; are journalists utilising this act in their work; and how is the practice environment for journalists? Bearing these questions in mind, this study, using an exploratory methodology, reviewed the operation of Freedom of Information Act (FOIA) in Nigeria since 2011 and its utilisation by journalists. The result reveals that FOIA has low utilisation among journalists while the Act is yet to take firm roots in the cultural environment of journalism practice in the country. It also showed that the Act is hampered by existing legal and administrative barriers in the country while important stakeholders such as civil servants, and MDAs, have low levels of FOIA awareness. The study concludes that important as the FOI is, its impact is yet to be fully felt in journalism practice in Nigeria. The study recommends that important journalism stakeholders such as tertiary institutions, the Nigerian Union of Journalists (NUJ), employers, Newspaper Proprietors Association of Nigeria (NPAN), and Civil Society Organisations (CSO) etc., should increase their awareness creation on FOIA to make journalists use it more and impact our society better.